On sweat : On dizziness ; and, On fatigue - Theophrastus. (Philosophia Antiqua, 2003)
This volume contains modern editions of three physiological treatises by Theophrastus of Eresus, who was Artistotle's pupil and successor as head of the Peripatetic School. The treatises are concerned with human phenomena of sweat, dizziness and fatigue, and exhibit close ties to the contemporary medical literature. The Greek text of each treatise is based on a new reading of the principal manuscripts. The text is accompanied by an apparatus of parallel text and variant readings. The excerpts of Photius, patriarch of Constantinople, are printed below the Theophrastean text in order to facilitate comparison. An English translation appears opposite the Greek text. There are brief notes to the translation, and a fuller commentary follows. Indices of important words and topics and a selective bibliography complete each edition.